Communication - McQuail, Denis (London ; New York : Longman, 1975)
There is hardly a sub-discipline in sociology to which the topic of this little book is not at least tangentially relevant, especially for those trained in the symbolic interaction tradition and those for whom society is best conceptualized as "a set of shared understandings". McQuail does an admirable job of making this book more pertinent to the theoretical and empirical interests of mainstream sociologists. The book gives special attention to the structure of communication in small informal groups, in the formal settings of complex organizations, in the social networks of neighborhoods and communities, and in the complex chains of contact within societal institutions.
Includes index.
Includes bibliographical references: p. 209-224.
rpm 16/07/2018
Loans
Keywords: Communication